1997
DOI: 10.1002/j.2334-5837.1997.tb02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned Applying Model‐Based System Engineering Methods to a Strategic Planning Activity

Abstract: A recent strategic planning effort at the Savannah River Nuclear Site successfully utilized a model-based system engineering approach to develop a plan for the disposition of stored nuclear waste material. In the beginning, many team members, as well as program management, did not understand how system engineering methods and tools could possibly help the team accomplish its objectives. The perception was that a system engineering approach was overkill -all that was needed were domain experts, a facilitator, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The CORE  PC-based tool was used for requirement development. Baker (Baker, 1997) showed that the tool provided an improved traceability and evolution of originating requirements.…”
Section: Capturing and Verification Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CORE  PC-based tool was used for requirement development. Baker (Baker, 1997) showed that the tool provided an improved traceability and evolution of originating requirements.…”
Section: Capturing and Verification Processesmentioning
confidence: 99%
“…The CORE  software was used for giving a graphic presentation of FFBDs and allocated requirements, functional interfaces, and gaining insight into derivation of interfaces (Baker, 1997). It also enables group participation to make design suggestions in concurrent engineering.…”
Section: Capturing and Verification Processesmentioning
confidence: 99%
See 1 more Smart Citation